2002
DOI: 10.1021/cm010558l
|View full text |Cite
|
Sign up to set email alerts
|

Indium−Vanadium Oxides Deposited by Radio Frequency Sputtering:  New Thin Film Transparent Materials for Li-Insertion Electrochemical Devices

Abstract: Thin films of mixed In/V oxides have been obtained by reactive RF sputtering. Their optical and electrochemical performances have been investigated in order to determine their possible applications in electrochromic devices as optically passive ion-storage layers. The targets used have been made of In 2 O 3 and V 2 O 5 powders mixed in different In/V ratios in a reactive sputtering atmosphere. Cyclic voltammetry and chronopotentiometry studies of these films have been performed. The films demonstrate high ion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…The presence of shake-up satellites is characteristic of Ni(II) paramagnetic species in octahedral and tetrahedral coordination, as reported in early literature findings, 21 where it has been shown that the satellite number, intensity and energy separation from main peaks are variable to a large extent in different species. Based on the phase diagram of the NiO-V 2 O 5 system 22 and on the experimental conditions for sample production adopted here, the present sample composition could be expected to be a mixture of Ni VO 3 and V 2 O 5 . V 2 O 5 has been characterized thoroughly by photoemission in several publications.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of shake-up satellites is characteristic of Ni(II) paramagnetic species in octahedral and tetrahedral coordination, as reported in early literature findings, 21 where it has been shown that the satellite number, intensity and energy separation from main peaks are variable to a large extent in different species. Based on the phase diagram of the NiO-V 2 O 5 system 22 and on the experimental conditions for sample production adopted here, the present sample composition could be expected to be a mixture of Ni VO 3 and V 2 O 5 . V 2 O 5 has been characterized thoroughly by photoemission in several publications.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Relevant issues have been addressed on intercalated electrodes, by conventional or more recently synchrotron radiation-excited photoemission. 9,10 The versatility of XPS is exemplified in studies on the electronic structure of well-established electrochromic materials such as WO 3 , 11 on in situ investigations on largearea electrode materials 12 and on the determination of the surface composition of reactive electrodes as a consequence of the use of different electrolytes or solutions. 13 The aim of our paper is to monitor the evolution of some aspects of Li insertion reaction that are mostly relevant to the performance of an intercalation electrode.…”
Section: Introductionmentioning
confidence: 99%
“…A large surface area and easy transport are required to achieve high charge/discharge rate. 6,7 The diffusion coefficient of Li in V 2 O 5 is about 10 11 -10 13 cm 2 /sec 8,9 , which is relatively small, so that a large surface area and a short diffusion distance are desired to achieve such abilities. It is clear that nanostructures, such as nanorod arrays, are advantageous for these applications to make such properties improved.…”
Section: Introductionmentioning
confidence: 99%
“…The time derivative of any variable is thus given, for example, as ∂c ∂τ = λjωc exp[ jωτ] [29] Because the terms exp[ jωτ] multiply all of the order λ terms in the equations, these terms can be omitted when writing down the equations for the order λ terms. With these notational changes, equations 20-26 can be replaced with…”
Section: Analysis and Simulation Of Electrochemical Impedance Spectromentioning
confidence: 99%